2007
DOI: 10.1158/0008-5472.can-06-4682
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Factor-4 Variant Chemokine CXCL4L1 Inhibits Melanoma and Lung Carcinoma Growth and Metastasis by Preventing Angiogenesis

Abstract: The platelet factor-4 variant, designated PF-4var/CXCL4L1, is a recently described natural non-allelic gene variant of the CXC chemokine platelet factor-4/CXCL4. PF-4var/CXCL4L1 was cloned, and the purified recombinant protein strongly inhibited angiogenesis. Recombinant PF-4var/CXCL4L1 was angiostatically more active (at nanomolar concentration) than PF-4/CXCL4 in various test systems, including wound-healing and migration assays for microvascular endothelial cells and the rat cornea micropocket assay for ang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 49 publications
7
85
0
Order By: Relevance
“…2D), indicating a stronger angiostatic activity of CXCL4L1/PF-4var 47-70 compared with CXCL4/PF-4 . For comparison, inhibition of endothelial cell migration was obtained at 20 nmol/L CXCL4/PF-4 or 1 nmol/L CXCL4L1/PF-4var, confirming previously published data (18,19). This allowed us to conclude that CXCL4L1/PF-4var is equally angiostatic as the intact chemokine.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…2D), indicating a stronger angiostatic activity of CXCL4L1/PF-4var 47-70 compared with CXCL4/PF-4 . For comparison, inhibition of endothelial cell migration was obtained at 20 nmol/L CXCL4/PF-4 or 1 nmol/L CXCL4L1/PF-4var, confirming previously published data (18,19). This allowed us to conclude that CXCL4L1/PF-4var is equally angiostatic as the intact chemokine.…”
Section: Discussionsupporting
confidence: 89%
“…As a control, CXCL4/PF-4 and CXCL4L1/PF-4var were also tested in this assay. The results confirm that CXCL4L1/PF-4var inhibits endothelial cell migration at 1 nmol/L, being therefore a 20-fold more potent inhibitor than CXCL4/PF-4 (18,19). Next, it was found that both PF-4 peptides (from 5 nmol/L onwards) significantly inhibited FGF-2-induced HUVEC motility as observed by time-lapse microscopy ( Fig.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…10,22,25,[51][52][53][54][55] The antitumor activity of IP-10 alone is usually moderate, but can in some cases be markedly increased by combined therapy, in particular with interleukin-2 and interleukin-12.…”
Section: Discussionmentioning
confidence: 99%